Optimizing strength training - Kraemer, W. J.; Fleck, S. J. (Human Kinetics, 2007)
The strength training strategy of linear periodization has long been recognized as an efficient system of resistance training. But—until now—no one had researched and explored the potential benefits of a nonlinear periodization training program.